Uji Ketahanan in Vitro Klon-klon Kentang Hasil Persilangan Kentang Kultivar Atlantic dan Granola terhadap Penyakit Layu Bakteri (Ralstonia solanacearum) dan Busuk Lunak (Erwinia carotovora) - Awang Maharijaya; Muhammad Mahmud; Agus Purwito (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
Several bacterial pathogens can cause diseases of potato. Ralstonia solanacearum and Erwinia carotovora are those of the world’s most important diseases of potato, especially in tropical climates. This experiment was aimed to obtain putative potato cultivars having good tolerance to bacterial wilt caused by R. solanacearum and soft rot caused by E. carotovora. Two adopted potato cultivars in Indonesia, cv. Atlantic (2n=4X=48) and cv. Granola (2n=4X=48), were used as parents. The experiment was arranged in a Randomized Complete Design. Test for tolerance was perfomed in vitro using BF15 as susceptible control and Solanum stenotonum as tolerance control. The result showed that there was high diversity of tolerance level to both R. solanacearum and E. carotovora. Some clones showed good tolerance level as compared to cv. Atlantic and cv. Granola, but none showed that as compared to S. stenotonum.